2019
DOI: 10.21203/rs.2.10158/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Use of potentially inappropriate medication and polypharmacy in older adults: a repeated cross-sectional study

Abstract: Background: Potential inappropriate medications (PIM) have an increased risk for adverse drug reactions (ADR) in an older adult population. With increasing age, multimorbidity is growing along with the use of medications. For several years, polypharmacy has been found to increase in western societies. Polypharmacy is associated with an increased risk of ADR. In this study, we analysed the prevalence of PIM in an older adult population and in different strata of the variables age, gender, number of chronic cond… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…A systematic review reported that, globally, there is large heterogeneity in the definition of polypharmacy ranging from numerical counts only, numerical counts for a given therapeutic setting or duration [15]. A cross-sectional study has investigated the prevalence of polypharmacy in Sweden, divided into 2 strata of no use to use of 4 medications (i.e., no polypharmacy) and use of 5 or more medications (i.e., polypharmacy) [16]. In Japan, the "Guidelines for Medical Treatment and Its Safety in the Elderly 2015" reported that an increase in occurrence of adverse drug events (ADE) is associated with the number of medications, such as 6 or more kinds of medication [17].…”
Section: Definition Of Polypharmacymentioning
confidence: 99%
“…A systematic review reported that, globally, there is large heterogeneity in the definition of polypharmacy ranging from numerical counts only, numerical counts for a given therapeutic setting or duration [15]. A cross-sectional study has investigated the prevalence of polypharmacy in Sweden, divided into 2 strata of no use to use of 4 medications (i.e., no polypharmacy) and use of 5 or more medications (i.e., polypharmacy) [16]. In Japan, the "Guidelines for Medical Treatment and Its Safety in the Elderly 2015" reported that an increase in occurrence of adverse drug events (ADE) is associated with the number of medications, such as 6 or more kinds of medication [17].…”
Section: Definition Of Polypharmacymentioning
confidence: 99%